Topical corticosteroid abuse on face: A clinical, prospective study - Kaur Brar Balwinder; Nidhi Kamra; Sukhmani Kaur Brar (Our Dermatology Online, 2015)
Introduction: Topical corticosteroids are widely misused and uncontrolled use of topical corticosteroids leads to undesirable adverse effects on facial skin. Aim: The aim of this study was to assess cutaneous manifestations of topical corcticosteroid abuse on the face and to analyse various factors contributing to the same. Materials and methods: A total of 100 patients with facial dermatoses using topical corticosteroids for a minimum period of 1 month attending the outpatient department from a period of January 2013 to September 2014 were enrolled for the study. Details about the usage of topical corticosteroids and their adverse effects were recorded. Results: Majority of the patients were females (68%). The most common indication for use was acne (68%), followed by melasma (22%). Most of the patients used them for duration of less than 6 months and most commonly misused steroids were of potent type. The commonest side effect was acneiform eruption (56%) followed by steroid dependent facies (26%). Other adverse effects like hypertrichosis, telangiectasia and premature aged appearance was seen with longer duration of steroid use. Conclusion: Misuse of topical corticosteroids is rampant and urgent, quick steps are required to increase the awareness and for better management of its adverse consequences.